Communication patterns in the implementation of the Kampus Mengajar program under the MBKM policy - Rosalin, Elin; Kurniatun, Taufani C.; Sutarsih, Cicih; Triatna, Cepi; Hartini, Nani; Sunaengsih, Cucun (Indonesian Research Journal in Education |IRJE|, 2025)
This research attempted to analyze the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy of the Kampus Mengajar program and its improvement strategies based on the Edward III approach. This qualitative research was conducted through an exploratory approach. The authors chose the Faculty of Education, Universitas Pendidikan Indonesia, as the object of this research, with students, partner institutions, and university MBKM managers as the unit of analysis. Data analysis was carried out using NVivo 12 software based on the variables and indicators that had been prepared. The results indicate that communication has a significant role in program implementation. Communication patterns in the policy context must meet the aspects of information transmission, clarity of information, and consistency of information, where the policies communicated implications must be precise, accurate, and consistent so that decision-makers and implementers are more consistent in implementing.